Rice Knowledge Management Portal for Technology Dissemination: A Case Study for Haryana, Punjab and Uttarakhand States - D. R. Das, P. S Pandey, A. K. Mishra, S. N. Meera (Indian Journal of Extension Education, 2022)
,,